2019
DOI: 10.1097/ogx.0000000000000668
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch Repair Deficiency Identifies Patients With High-Intermediate–Risk (HIR) Endometrioid Endometrial Cancer at the Highest Risk of Recurrence: A Prognostic Biomarker

Abstract: (Abstracted from Cancer 2019;125:398–405) More than 70% of patients diagnosed with endometrial cancer (EC) are stage I, and such early-stage disease has good outcomes, with reported 5-year survival rates of 90%. However, a small subgroup has been identified—the so-called high-intermediate–risk (HIR) EC—which has relatively high local and distant recurrence rates, resulting in poor survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Recurrent endometrial cancer (REC) is a great clinical challenge in the management of EC. Approximately 10-15% of patients with early-stage EC develop tumor recurrence after staged surgery, and among women with EC, there is a high incidence of tumor recurrence in the two to three years following systemic therapy [4][5][6]. Early EC can be screened out and cured at an early stage, but REC predicts poor prognosis [7].…”
Section: Introductionmentioning
confidence: 99%
“…Recurrent endometrial cancer (REC) is a great clinical challenge in the management of EC. Approximately 10-15% of patients with early-stage EC develop tumor recurrence after staged surgery, and among women with EC, there is a high incidence of tumor recurrence in the two to three years following systemic therapy [4][5][6]. Early EC can be screened out and cured at an early stage, but REC predicts poor prognosis [7].…”
Section: Introductionmentioning
confidence: 99%
“…We found that EEC was FIGO grade 3 only in this study, the most patients received adjuvant therapy. In contrast, in the study by Backes et al [27], MSI was associated with a signi cantly worse recurrence-free survival, in which EEC was FIGO grade1-3, and patients receive adjuvant at a much lower rate. Therefore, We assume that more adjuvant therapy is an important in uencing factor on the prognostic value of MSI.…”
Section: Discussionmentioning
confidence: 73%
“…15 studies were retrospective cohort studies [8, 11, 13-19, 21, 23-27], and 2 studies were clinical trials [7,22]. 8 studies assessed MSI using quasimonomorphic mononucleotide markers [7,8,[15][16][17][18][19]21], and 9 studies assessed MSI using immunohistochemistry [11,13,14,[22][23][24][25][26][27]. The pooled HR for patients with EEC shown that MSI was signi cantly associated with shorter overall survival [HR = 1.37, 95% CI (1.00-1.86), p = 0.048].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stage III/IV patients with dMMR had significantly decreased recurrence-free survival (47.4% vs. 3.4%) despite receiving similar adjuvant therapies. This relationship was further investigated in high-intermediate risk patients, with MMR defects being associated with worse recurrence rates (28% vs. 11%), with distant recurrences being particularly notable (14.1% vs. 3%) (35). This difference held even when excluding isolated vaginal recurrences (18.8% vs. 4.5%).…”
Section: Endometrial Cancermentioning
confidence: 97%